Alemtuzumab induction in simultaneous pancreas and kidney transplantation. (8th August 2013) - Zachariah, Mareena; Gregg, Austin; Schold, Jesse; Magliocca, Joseph; Kayler, Liise K.
Abstract: Background: Alemtuzumab (AZ) is a monoclonal anti‐CD52 antibody used as an induction agent in organ transplantation. Few studies have analyzed this agent in the context of simultaneous kidney–pancreas transplantation (SPKT). Methods: We examined US registry data of SPKT recipient outcomes from January 2002 to October 2009 stratified by induction agent including AZ, other T‐cell–depleting agents combined (T cell), IL2 receptor blockade (IL‐2RAb), and no induction (none). Results: Of 6860 SPKT recipients, induction therapy was AZ in 10%, T cell in 49%, IL‐2RAb in 18%, and none in 22%. On multivariate analysis, there were no significant differences in overall patient survival, pancreas or renal allograft survival, or delayed renal graft function for the three induction groups compared with no induction. Rehospitalization within six months of transplantation occurred more often with AZ (51%) T cell (52%), and IL‐2RAB (45%) compared with none (41%; p < 0.0001). On multivariate analysis, there was a significant higher odds of six‐month rehospitalization with AZ (aOR 1.40, 95%CI 1.14–1.71), IL‐2RAb (aOR 1.20, 95%CI 1.01–1.42–1.20), and other T‐cell–depleting agents (aOR 1.50, 95%CI 1.31–1.73) compared with none. Median length of stay was significantly shorter in the AZ (8 d) compared with the IL‐2RAb (9 d), T cell (10 d), and none (10 d) groups (p < 0.0001). Conclusions: There are no differences in patient, pancreas or renal allograft survival using AZ induction. AZ may confer an advantage in the perioperative period as evidenced by a decreased hospital length of stay. However, this benefit may be lost due to more frequent rehospitalizations.